The influence of heat stress and powder of jaloh leaves supplementation into commercial fish feed on body weight gain, hematokrit level and malondialdehid content in the nila’s liver - . Sugito; . Samadi; . Nurliana (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
The aims of this experiment are to find out the effect of temperature stress and jaloh leaves supplementation on body weight gain, hematocrit level, and malondialdehid (MDA) content in the liver tissues of nila fish (Oreochromis niloticus). A total of 80 fishes with the weight of 40-50 gr were randomly allocated into 8 treatments. The treatments consisted of P1 (no heat stress and no jaloh leaves supplementation); P2 (no heat stress and 5% of jaloh leaves supplementation) ; P3 (no heat stress and 10% of  leaves supplementation); P4 (no heat stress and 15 % of  leaves supplementation); P5 (heat stress and no jaloh leaves supplementation); P6 (heat stress and 5% of  jaloh leaves supplementation); P7 (heat stress and 10% of  jaloh leaves supplementation); P8 (heat stress about 35 ± 1oC  for 4 h per day in 30 days and 15% of  jaloh leaves supplementation). The body weight was measured from 1d to 31d. Blood samples, lever tissues and statistical analysis were conducted on 31d. The results of the experiments indicated that supplementation of fish feed with jaloh leaves 5-15% had negative effects on body weight gain. On the other hand, supplementation of jaloh leaves 5-10% on commercial fish feed had positive effects on performances and immune system of experiment fishes